ПЕРЕВАГИ ТА НЕДОЛІКИ ЗАСТОСУВАННЯ ЕКОЛОГІЧНИХ ПОДАТКІВ ДЛЯ ЗНИЖЕННЯ РІВНЯ ЗАБРУДНЕННЯ ДОВКІЛЛЯ - Шако, Олена Анатоліївна (Науковий журнал «Світ фінансів», 2017)
Шако О. А. Переваги та недоліки застосування екологічних податків для зниження рівня забруднення довкілля. Досліджено теоретичні основи екологічного оподаткування. Проаналізовано вплив екологічних податків на поведінку суб’єктів господарювання. Розглянуто статичну та динамічну ефективність екологічних податків для зниження рівня забруднення довкілля та забезпечення раціонального природокористування. Обґрунтовано теоретичні підходи до застосування екологічних податків для вирішення конкретних екологічних проблем виходячи з виявлених переваг та недоліків їх застосування. Шако Е. Преимущества и недостатки применения экологических налогов для снижения уровня загрязнения окружающей среды. Исследованы теоретические основы экологического налогообложения. Проанализировано влияние экологических налогов на поведение субъектов хозяйствования. Рассмотрены статическая и динамическая эффективность экологических налогов для снижения уровня загрязнения окружающей среды и обеспечения рационального природопользования. Обоснованы теоретические подходы к применению экологических налогов для решения конкретных экологических проблем исходя из выявленных достоинств и недостатков их применения. Shako O. Advantages and disadvantages of environmental tax for reduce pollution. The system of environmental taxes is an integral part of the national tax system. Its purpose is to solve some important environmental, economic and socialproblems. In particular, the problems that can be solved by creating an effective system of environmental taxes related to price incentives taxpayers to reducing pollution, stimulate energy and resource efficiency and compensation for environmental damage to society. The current system of environmental taxes in Ukraine, although recently undergone signifi cant changes Reformation, however, in quality and functional meaning it does not meet the criteria for environmental, fi scal and administrative effi ciency. The introduction of the Tax Code of Ukraine environmental tax and the tax reform of 2014 did not provide a logical conclusion of environmental taxation system, and became only the first step of transformation to create the contemporary realities of environmental taxation system able to effectively influence the level of pollution. Because environmental issues in Ukraine has become especially pressing because of how strong anthropogenic impact on the environment and the lack of long-term state adequate response to this danger posed. Considering the above for Ukraine is extremely important on improving environmental taxes as from a theoretical point of view, and based on substantial practical signifi cance. In this context, the purpose of the article was put research advantages and disadvantages of the use of environmental taxes that will provide the most effective solution for their application. Advantages the use of environmental taxes include static and dynamic efficiency of environmental taxes. Factors that reduce the effectiveness of environmental taxes include varying environmental damage, depending on the geographic location of sources of emissions; dependence manifestation of desired behavioral effects on the structure of decision-making enterprises; encouraging taxpayers to evade paying taxes; regressivity; impact on the international competitiveness of products. The introduction of direct taxes on environmental pollution associated with signifi cant transaction costs. To reduce such costs in the practice of environmental taxation, indirect taxes are used as inputs to and the finished product.